Point-bar development under human impact: case study on the Lower Tisza River, Hungary - Nagy, Judit; Kiss, Tímea (Geographica Pannonica, 2020)
Point-bars are the most typical forms of floodplains; therefore, any change in the fluvial environment is reflected in their formation. We aimed to analyse the morphological characteristics and influencing factors of their formation along the Lower Tisza River (Hungary). Before the 1930-60s the morphological characteristics of point-bars were affected primarily by natural factors. However, after revetment constructions, the lateral migration of meanders ceased and channel became significantly narrower, therefore point-bar widths have decreased from 68 m to 19 m. Besides, vertical accumulation became dominant, thus, the youngest active point-bars are narrow and high.